A Mathematical Model Of Unsteady Water Movement In Sections Of Main Canals Limited By Hydraulic Structures - А. V. Kabulov, A. J. Seytov, A. A. Kudaybergenov (International Journal of Advanced Science and Technology, 2020)
A mathematical model of unsteady water movement in sections of main canals limited by hydraulic structures has been developed. The statement of problems of optimal control of water distribution in the main canals is also developed. A fundamental solution is obtained for a one-dimensional differential equation describing the unsteady water movement in sections of main canals.